Cover Feature: Catalyst Stability Benchmarking for the Oxygen Evolution Reaction: The Importance of Backing Electrode Material and Dissolution in Accelerated Aging Studies (ChemSusChem 21/2017). Issue 21 (27th October 2017) - Geiger, Simon; Kasian, Olga; Mingers, Andrea M.; Nicley, Shannon S.; Haenen, Ken; Mayrhofer, Karl J. J.; Cherevko, Serhiy
Abstract : The Cover Feature demonstrates the importance of differentiation between several degradation phenomena that appear in lab‐scale accelerated stress tests for oxygen evolution reaction (OER) materials. The provided insights are essential for interpretation of electrochemical degradation results and eventually for identifying best catalysts. More information can be found in the Communication by Geiger et al. onpage 4140 in Issue 21, 2017 (DOI:10.1002/cssc.201701523 ).